Cosserat mechanics in Earth sciences - Garagash, Igor Alexandrovich; Nikolaevskiy, Victor Nikolaevich (Computational Continuum Mechanics, 2009)
Cosserat mechanics takes into account the rotational dynamics of particles composing a continuous medium, which is of special importance in the case of kinematics. For this purpose, in accordance with Newton’s third law, it is necessary to create a continuum equation for the moments of momentum of a unit volume of the medium. Such an equation was first constructed in the book by Е. and F. Cosserat [1] who considered the dynamics of elastic deformable media. Correct deduction of the external moments corresponding to the volume rotation as a whole was made. The phenomena that can be explained by the rotational dynamics of the individual particles composing the environment - fragments of rock massifs or whirlwinds of a turbulent atmosphere - are frequently observed in nature. The paper presents some examples illustrating the capabilities of Cosserat mechanics falling outside the scope of traditional University lecture courses. To this end, its classical form is supplemented by viscous, plastic or other rheological properties.